2008
DOI: 10.1167/8.7.11
|View full text |Cite
|
Sign up to set email alerts
|

Selective mechanisms for simple contours revealed by compound adaptation

Abstract: Neurons in the early stages of visual processing are often thought of as edge detectors for different orientations. Here we investigate the existence of detectors for specific combinations of edges-detectors for specific curvatures. Previous attempts to demonstrate such detectors through aftereffects have ultimately been explained by adaptation to local orientation rather than curvature per se. To control for local aftereffects, we adapted one patch of visual field to two adjacent gratings presented as an obtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 45 publications
5
33
0
Order By: Relevance
“…This is consistent with experimental results (Loffler et al, 2003) showing that RF discrimination sensitivity is affected most strongly when points of convex curvature maxima are occluded, although other parts of the contour have been shown to play a non-trivial role (Poirier and Wilson, 2007; Hancock and Peirce, 2008; Bell et al, 2010). These observations were, however, for RFs with low amplitude, which do not contain concavities.…”
Section: Model For Shape Processingsupporting
confidence: 88%
“…This is consistent with experimental results (Loffler et al, 2003) showing that RF discrimination sensitivity is affected most strongly when points of convex curvature maxima are occluded, although other parts of the contour have been shown to play a non-trivial role (Poirier and Wilson, 2007; Hancock and Peirce, 2008; Bell et al, 2010). These observations were, however, for RFs with low amplitude, which do not contain concavities.…”
Section: Model For Shape Processingsupporting
confidence: 88%
“…By showing that RF discrimination thresholds increase disproportionately when introducing small gaps at the peaks of RF patterns, Loffler et al (2003) suggested that points of maximum convex curvature play a key role in RF discrimination. Findings from lateral masking experiments are consistent with the hypothesis of maximum curvature dominance (Habak et al, 2004) although other studies have highlighted a non-trivial role of other parts of the contour (Poirier and Wilson, 2007; Hancock and Peirce, 2008; Bell et al, 2010). If local curvature maxima were relied upon, one may expect shape detection sensitivity to increase with increasing shape amplitude and frequency as these manipulations increase the maximum curvature, but this is inconsistent with the data (Figures 3A,B).…”
Section: Discussionsupporting
confidence: 77%
“…Subsequent experiments by Sigel & Nachmias (1975), and Hayman & Allan (1980) refuted both of these findings, showing that they could be explained by local orientation dependent aftereffects and patterns of visual fixation. Recently Hancock & Peirce (2008) showed that apparent curvature can be influenced by adaptation, in a manner consistent with the existence of curvature dependent mechanisms. The same experiments, however, did not show any evidence of contrast adaptation in these putative mechanisms.…”
Section: Discussionmentioning
confidence: 62%